Money talks with Asian giants thoughts of our economics leaders & business titans revealed - Lim, Wing Hooi (AMX Capital, 2011)
This is a simple to read quote book of 15 Asian Giants who have made headlines around the world. Revealing their thoughts in five clearly presented chapters spanning from self- management to economic and finance, this book is aimed to inspire future leaders of what it takes to be at the top of their game!